2023
DOI: 10.3390/ijerph20032174
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the Sport Education Model to Promote Healthy Lifestyles in University Students: A Randomized Controlled Trial

Abstract: Although studies on sports performance, leadership abilities, group cohesion, and learning motivation have revealed that the sport education model contributes considerably to the development of healthy lifestyles, few studies have explored the development of healthy lifestyles from an educational intervention perspective. This study fills this gap in the literature. In addition, studies have mostly recruited elementary or middle school students; few have explored the effectiveness of sport education for colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…On the other hand, the sports education model (SEM) can promote health more than the conventional education model (Liao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the sports education model (SEM) can promote health more than the conventional education model (Liao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, breakthrough innovations that trigger healthy lifestyle models in employing physical education intermediaries. It is also useful for teachers who need to implement specific teaching strategies to cultivate and reinforce exercise habits and healthy behaviors among students (Liao et al, 2023).…”
Section: Graph 1 Comparison Between Physical Activity and Stress Levelsmentioning
confidence: 99%
“…Face-toface learning activities can lead students to focus on the impact of personal relationships with family and friends, feelings and emotions, and experiences of stress and anger that can impact mental health (Rocamora et al, 2023). Embedding socially relevant learning activities into school content, organization, and curriculum can help increase students' sense of enjoyment, participation, and achievement, which is essential for increasing knowledge and awareness about mental health (Haycock et al, 2020;Liao et al, 2023;Rodríguez Macías et al, 2021). Hence, this finding can be used as a reference, especially for educators, both lecturers and teachers in schools, to be able to take a spiritual approach and invite students to do activities they like, such as exercise and recreation, to trigger a sense of enthusiasm in students to continue to improve their fitness degree; therefore, this will have an impact on mental health, which can affect students' stress levels much lower.…”
Section: Graph 1 Comparison Between Physical Activity and Stress Levelsmentioning
confidence: 99%
“…Additionally, maintaining a healthy lifestyle during these critical years is a significant global concern. Research has shown that a substantial proportion of students experience weight gain during their first year at a university due to stress, unhealthy dietary choices, and decreased physical exercise [ 5 , 7 , 8 ]. The pervasive use of digital devices, such as cell phones and computers, contributes to a sedentary lifestyle, reducing motivation for physical activities and increasing the risk of weight gain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%